HUBUNGAN RELIGIUSITAS DENGAN FLOW AKADEMIK PADA SISWA SMP YPM 4 BOHAR - Alissa Elma Zakiyah Ar Rahma; Dwi Nastiti (Fakultas Psikologi Universitas Tarumanagara, 2023)
This research is motivated by the problem of the academic flow phenomenon experienced by students, such as students having difficulty concentrating, being less happy when they get homework, and students who will learn if they get encouragement from parents or teachers. This research aims to determine the relationship between religiosity and academic flow in students. This research uses a quantitative correlational type of research. The number of subjects used in this research was 234 students of Junior High School YPM 4 Bohar, and the sample was determined using the proportionate stratified random sampling technique. Research data was collected using a religiosity and academic flow scale compiled by the researcher himself. Analysis of the results of this research used a correlation test assisted by the JASP application program version 0.16. The results of this research data analysis show a correlation coefficient value of 0.582 with a significance of 0.001 (< 0.05), which means the research hypothesis is accepted. There is a significant positive relationship between religiosity and academic flow in YPM 4 Bohar Middle School students. In this study, the religiosity factor had an influence of 44.6% in increasing academic flow.